Analysis of the profile of blood donors in a blood bank of a private medical college of Kolkata - Haldar, Debdutta; Majumdar, Kunal Kanti; Karir, Shilpa; Chakraborty, Arun Kumar; Dey, Ankita; Mandal, Asok Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Blood is the only oxygen transporter in the body and is crucial in saving lives. Research has failed to find a true substitute for blood and blood components and depends on human donors. There are several infectious and non-infectious risks associated with transfusion. An unsafe transfusion is very costly from both human and economic points of view. In that perspective the present study is aimed to assess the profile of blood donors. The objectives of the study were to assess the profile of blood donors as per records of Blood Bank of a private medical college of Kolkata and to find out the prevalence and trends of transfusion transmitted infections among those donors. Methods: A record based cross sectional study was conducted for the period May 2013 to April 2016 at Blood Bank of a private medical college and information regarding 5383 blood donor’s profile were collected and analysed. Results: The total donors were found to be 5383 out of which (87.72%) were voluntary donors and (12.28%) replacement donors. The donors had a male predominance (79.84%). The most available blood group was B+ (49.42%) and the least available blood group was A- (0.38%). The commonest transfusion transmitted infection was Hepatitis B (1.11%) followed by Hepatitis C (0.28%) and HIV (0.21%). The transfusion transmitted infections (TTI) shows a decreasing trend over the 3 years. Conclusions: The voluntary donors have increased over the 3 years but there is always a male predominance. The pattern of TTIs in the blood bank depicts the national trend too.